Fibrinolytic Agents in Thromboembolic Diseases: Historical Perspectives and Approved Indications - Rashedi, Sina; Greason, Christie M.; Sadeghipour, Parham; Talasaz, Azita H.; O'Donoghue, Michelle L.; Jimenez, David; Monreal, Manuel; Anderson, Christopher D.; Elkind, Mitchell S. V.; Kreuziger, Lisa M. Baumann; Lang, Irene M.; Goldhaber, Samuel Z.; Konstantinides, Stavros V.; Piazza, Gregory; Krumholz, Harlan M.; Braunwald, Eugene; Bikdeli, Behnood (Seminars in Thrombosis and Hemostasis, 2024)
Fibrinolytic agents catalyze the conversion of the inactive proenzyme plasminogen into the active protease plasmin, degrading fibrin within the thrombus and recanalizing occluded vessels. The history of these medications dates to the discovery of the first fibrinolytic compound, streptokinase, from bacterial cultures in 1933. Over time, researchers identified two other plasminogen activators in human samples, namely urokinase and tissue plasminogen activator (tPA). Subsequently, tPA was cloned using recombinant DNA methods to produce alteplase. Several additional derivatives of tPA, such as tenecteplase and reteplase, were developed to extend the plasma half-life of tPA. Over the past decades, fibrinolytic medications have been widely used to manage patients with venous and arterial thromboembolic events. Currently, alteplase is approved by the U.S. Food and Drug Administration (FDA) for use in patients with pulmonary embolism with hemodynamic compromise, ST-segment elevation myocardial infarction (STEMI), acute ischemic stroke, and central venous access device occlusion. Reteplase and tenecteplase have also received FDA approval for treating patients with STEMI. This review provides an overview of the historical background related to fibrinolytic agents and briefly summarizes their approved indications across various thromboembolic diseases.
Keywords: fibrinolytic agents; plasminogen activator; thromboembolism